The Socialization of Class Action Research Implementation Based on Lesson Study - Siti Halidjah; Hery Kresnadi; Nuri Sidauruk (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2019)
The purpose of this PKM is to provide an understanding of the implementation of action-based classroom study research. The target audience in this activity is elementary school teachers in Pontianak City. There were 26 teachers involved and were representatives of several schools. The method of activities carried out in the form of socialization by presenting speakers who have competence in the field of classroom action research based on lesson study. From the results of community service activities with a focus on implementing action-based classroom study research, teacher's knowledge and understanding of the implementation of lesson study-based action research is getting better. In addition, the increasing interest of teachers to collaborate on lesson study in conducting research will be carried out because the stages contained in lesson study are simpler and help teachers be more thorough in carrying out classroom action research.